History of Studying Semantic Aphasia Mechanisms (Based on Materials from Lurian Archive) - Akhutina, T; Agris, A (KnE Life Sciences, 2018)
The scientific heritage of Alexander Luria is vast and not completely studied. His scientific archive includes a range of documents that academics have never encountered. We analyzed the history of Luria’s research of semantic aphasia, specifically as it is related to the impairment of visuospatial processing. For this purpose, we investigated unpublished archive materials dating back to 1928–1940, particularly the monograph ‘Parietal Aphasia’ from 1940. The literature regarding the history of the issue and neurophysiological and linguistic interpretations of semantic aphasia is discussed in detail by Luria. We also introduce Luria’s diagnostic manual for the semantic impairment of language and describe the syndrome structure of semantic aphasia. To conclude, we discuss the specificity of semantic aphasia analysis in the pre-war monograph compared to later studies. Keywords: semantic aphasia, visuospatial processing, temporal-parietal-occipital association area, A.R. Luria, neuropsychology, neurolinguistics, history of psychology